Maintenance of Trypanosoma cruzi, T. evansi and Leishmania spp. by domestic dogs and wild mammals in a rural settlement in Brazil-Bolivian border - Porfirio, Grasiela Edith de Oliveira; Santos, Filipe Martins; de Macedo, Gabriel Carvalho; Barreto, Wanessa Teixeira Gomes; Campos, João Bosco Vilela; Meyers, Alyssa C.; André, Marcos Rogério [UNESP]; Perles, Lívia [UNESP]; de Oliveira, Carina Elisei; Xavier, Samanta Cristina das Chagas; Andrade, Gisele Braziliano de; Jansen, Ana Maria; et al. (Elsevier, 2018)
Domestic dogs are considered reservoirs hosts for several vector-borne parasites. This study aimed to evaluate the role of domestic dogs as hosts for Trypanosoma cruzi, Trypanosoma evansi and Leishmania spp. in single and co-infections in the Urucum settlement, near the Brazil-Bolivian border. Additionally, we evaluated the involvement of wild mammals’ in the maintenance of these parasites in the study area. Blood samples of dogs (n = 62) and six species of wild mammals (n = 36) were collected in July and August of 2015. The infections were assessed using parasitological, serological and molecular tests. Clinical examination of dogs was performed and their feeding habits were noted. Overall, 87% (54/62) of sampled dogs were positive for at least one trypanosomatid species, in single (n = 9) and co-infections (n = 45). We found that 76% of dogs were positive for T. cruzi, four of them displayed high parasitemias demonstrated by hemoculture, including one strain types TcI, two TcIII and one TcIII/TcV. Around 73% (45/62) of dogs were positive to T. evansi, three with high parasitemias as seen by positive microhematocrit centrifuge technique. Of dogs sampled, 50% (31/62) were positive for Leishmania spp. by PCR or serology. We found a positive influence of (i) T. evansi on mucous pallor, (ii) co-infection by T. cruzi and Leishmania with onychogryphosis, and (iii) all parasites to skin lesions of sampled dogs. Finally, feeding on wild mammals had a positive influence in the Leishmania spp. infection in dogs. We found that 28% (5/18) coati Nasua nasua was co-infected for all three trypanosamatids, demonstrating that it might play a key role in maintenance of these parasites. Our results showed the importance of Urucum region as a hotspot for T. cruzi, T. evansi and Leishmania spp. and demonstrated that dogs can be considered as incidental hosts.
Keywords: Canine; Neglected diseases; Pantanal; Sentinels hosts; Trypanosomatids